Lie symmetry analysis, exact solutions and conservation laws for the time fractional modified Zakharov-Kuznetsov equation - Baleanu, Dumitru; İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa (Inst Mathematics & Informatics, 2017)
In this work, Lie symmetry analysis (LSA) for the time fractional modified Zakharov-Kuznetsov (mZK) equation with Riemann-Liouville (RL) derivative is analyzed. We transform the time fractional mZK equation to nonlinear ordinary differential equation (ODE) of fractional order using its point symmetries with a new dependent variable. In the reduced equation, the derivative is in Erdelyi-Kober (EK) sense. We obtained exact traveling wave solutions by using fractional D(xi)(alpha)G/G-expansion method. Using Ibragimov's nonlocal conservation method to time fractional nonlinear partial differential equations (FNPDEs), we compute conservation laws (CLs) for the mZK equation.
Keywords: modified Zakharov-Kuznetsov equation; Lie symmetry; Riemann-Liouville fractional derivative; exact solutions; conservation laws